2010
DOI: 10.4304/jltr.1.3.320-323
|View full text |Cite
|
Sign up to set email alerts
|

The Advantages and the Problems of Multimedia-aided English Reading Instruction

Abstract: Reading plays an important role in the process of language learning. In the modern society, teachers can apply the multimedia technology to assist the reading instruction. On the basis of the research of scholars in this or relevant field, this paper firstly centers on the advantages of multimedia-aided English reading instruction by comparison to the traditional instruction. And then the paper states the problems of the multimedia-aided English reading instruction in China to promote the application of multim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The rich interactive multimedia reading environment afforded by CAR stimulates readers' auditory and visual senses, increases their interest in reading, and enhances their motivation (Han, 2010). Electronic texts make readers independent and autonomous; rather than being confined to a textbook, they are able to explore the wealth of information available in the electronic reading environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The rich interactive multimedia reading environment afforded by CAR stimulates readers' auditory and visual senses, increases their interest in reading, and enhances their motivation (Han, 2010). Electronic texts make readers independent and autonomous; rather than being confined to a textbook, they are able to explore the wealth of information available in the electronic reading environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Respondents also suggested that speaking English opens the door for admission into various scholarships. Nearly 90% of Ethiopian learners know that English is extremely important, and almost 99% of them think that it will help them in their professional growth [7][8][9].…”
Section: Resultsmentioning
confidence: 99%
“…First, questionnaire was prepared in English and translated into mother tongues, which are the languages of students and their parents in the study areas. Questionnaire is a popular means of collecting all kinds of data in research [9][10]. Koul (ibid) further argued that questionnaire is widely used in educational research to obtain information about certain conditions and practices, and to inquire into opinions and attitudes of an individual or a group.…”
Section: Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some teachers may not have enough skill to incorporate technology tools because they did not attend any Information Technology training (Kumutha & Hamidah, 2014). According to Han (2010), training and support improve gradually and they contribute to the integration of technology and efficiency of the teachers' teaching methods. It is unfortunate that some teachers do not put their expertise to good use when they teach large classes where it is quite impossible for the teacher to use the improvised ways of teaching in a lesson due to the size constraint.…”
Section: Literature Reviewmentioning
confidence: 99%